Bioprinting Neural Systems to Model Central Nervous System Diseases. (22nd April 2020) - Qiu, Boning; Bessler, Nils; Figler, Kianti; Buchholz, Maj‐Britt; Rios, Anne C.; Malda, Jos; Levato, Riccardo; Caiazzo, Massimiliano
Abstract: To date, pharmaceutical progresses in central nervous system (CNS) diseases are clearly hampered by the lack of suitable disease models. Indeed, animal models do not faithfully represent human neurodegenerative processes and human in vitro 2D cell culture systems cannot recapitulate the in vivo complexity of neural systems. The search for valuable models of neurodegenerative diseases has recently been revived by the addition of 3D culture that allows to re‐create the in vivo microenvironment including the interactions among different neural cell types and the surrounding extracellular matrix (ECM) components. In this review, the new challenges in the field of CNS diseases in vitro 3D modeling are discussed, focusing on the implementation of bioprinting approaches enabling positional control on the generation of the 3D microenvironments. The focus is specifically on the choice of the optimal materials to simulate the ECM brain compartment and the biofabrication technologies needed to shape the cellular components within a microenvironment that significantly represents brain biochemical and biophysical parameters. Abstract : This progress report focuses on the recent developments of bioprinting approaches in the field of in vitro neural models. The treated topics cover the gold standards in neural model biofabrication, describing the used bioprinting technologies, the building blocks, and the recent and future applications in the field of advanced in vitro neural modeling.